Quantitative financial risk management - Miller, Michael B. (Michael Bernard), 1973- (Hoboken, New Jersey: John Wiley & Sons, Inc., 2019)
"Our modern economy depends on financial markets. When financial markets work, they allow people to buy homes and save for retirement; they allow companies to provide the goods and services that we enjoy and depend on. When financial markets don't work, companies fail, people lose their homes, lose their savings, and lose their jobs. Yet financial markets continue to grow in size and complexity and the management of financial risk has never been more important. Quantitative Financial Risk Management is designed to teach students and risk professionals about financial risk management with an emphasis on financial models and mathematical techniques. Each chapter provides numerous sample problems and end of chapter questions. The book provides clear examples of how these models are used in practice and encourages readers to think about the limits and appropriate use of financial models"--
Includes bibliographical references (pages 295) and index.
Keywords: Financial risk management